Pengaruh Strategi Pemasaran 4P (Produk, Harga, Lokasi, Promosi) dan Word Of Mouth terhadap Volume Penjualan di Attahira Fashion Tulungagung - Fran Siska Efelin; Anita Sumelvia Dewi; Angga Permana Mahaputra (International Forum of Researchers and Lecturers, 2023)
This research aims to explain and prove the hypothesis regarding the influence of product, price, location, promotion and word of mouth on sales volume at Attahira Fashion Tulungagung. This research uses a quantitative method with a Non Probability Sampling sampling technique with an accidental sampling method with a sample size of 60 people. The analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression test, t test (partial) and F test (simultaneous) as well as the determinant coefficient (R2) which was processed using the SPSS version 25 program. Conclusions were obtained from the research results. that partially the product has a positive and significant effect on sales volume, a significant t value of 0.000 <0.05 is obtained. Price partially has a positive and significant effect on sales volume, obtaining a significant t value of 0.044 < 0.05. Location partially has no effect on sales volume, obtaining a significant t value of 0.460 < 0.05. Promotion partially has a positive and significant effect on sales volume, obtaining a significant t value of 0.000 < 0.05. Word of mouth partially has no effect on sales volume, obtaining a significant t value of 0.437 < 0.05. Product, price, location, promotion and word of mouth simultaneously have a positive and significant effect on sales volume at Attahira Fashion Tulungagung by looking at the significant F value of 0.000 < 0.05.